1′-Methyl-2,2′′-dioxoindoline-3-spiro-2′-pyrrolidine-3′-spiro-3′′-indoline-4′,4′-dicarbonitrile - Ramesh, P. (International Union of Crystallography, 2009)
In the title compound, C(21)H(15)N(5)O(2), the pyrrolidine ring adopts a twist conformation. Both the oxindole rings are planar [maximum deviations of 0.076 (1) and 0.029 (1) Å in the two rings] and are oriented at a dihedral angle of 72.7 (1)°. The crystal structure is stabilized by C—H⋯O, N—H⋯O, N—H⋯N and C—H⋯π interactions.